Pengaruh Variasi Volume Media Filtrasi terhadap Efektivitas Pasir Malang dalam Menurunkan Kadar Besi (Fe) di Air Tanah Desa Bajarum - Maradona, Maradona; Amelia, Vera; Adji, Fengky F. (Innovative: Journal Of Social Science Research, 2025)
The well water in Bajarum Village contains high levels of dissolved iron (Fe), requiring filtration using Malang Sand. This study aims to analyze the effectiveness of Malang Sand in reducing Fe levels with varying filter media volumes. An experimental method was employed using two filtration systems that combined aeration and filtration techniques. Groundwater samples were collected from several wells and tested for Fe levels before and after filtration. The results showed that the filter with 50% Malang Sand reduced Fe by an average of 11.7 mg/L (73.87%), while the filter with 100% Malang Sand reduced Fe by an average of 15.69 mg/L (91.16%). Statistical analysis confirmed a significant reduction in Fe levels after filtration (p<0.05); however, no significant difference was found between the 50% and 100% media volumes (p>0.05). In conclusion, Malang Sand filtration effectively reduces Fe levels, but increasing the media volume does not result in a significant difference.